2011
DOI: 10.1002/cphc.201100252
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Plasmon‐Coupled Emission of Rhodamine 110 in a Silica Nanolayer

Abstract: The first observation of strong directional surface-plasmon-coupled emission (SPCE) of Rhodamine 110 in silica nanofilms deposited on silver nanolayers is reported. The preparation of the material is described in detail. The intensity of SPCE exceeds 10 times that of free space fluorescence and total linear light polarization in the SPCE ring is observed. A new experimental setup and an original data collection method is presented. Our material completely preserves its fluorescence properties for at least eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…This procedure has been described in detail. 6 SPCE and F-SE were measured with the SPCE spectrofluorometer designed and constructed in our laboratory (Figure 1a). Similar setup was presented in other papers.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure has been described in detail. 6 SPCE and F-SE were measured with the SPCE spectrofluorometer designed and constructed in our laboratory (Figure 1a). Similar setup was presented in other papers.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Previously, it has been found that hybrid matrix forms a friendly environment for effective SPCE observation. 6 The change in the profile of absorption spectrum evidence the aggregation process developing with the increase in dye concentration. In the case of less concentrated samples (C R110 ≤ 0.002 M) the presence of higher order aggregates in silica nanolayers can be neglected, and it can be assumed that the analyzed system consists only of monomers and dimers.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This phenomenon has been used to develop sensing platforms promising far superior sensitivity and signal collection efficiency (>50% signal detection efficiency), in comparison to conventionally used detection methods such as fluorescence which is an isotropic phenomenon (<1% signal detection efficiency) [2][3][4]. Such platforms have already been used for the successful detection and sensing of many analytes both of biological and chemical in origin [5][6][7][8][9]. SPCE is a polarization dependent phenomenon where, only p-polarized incident light leads to the generation of the surface plasmons on the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…19 With respect to the dielectric space layer, the materials involved in majority of published work are inert silica shell, [20][21][22] polyelectrolyte multilayers obtained by layer-by-layer (LBL) technique, 23,24 polymers, 25,26 or prototypical biomolecules (D-biotin, complementary DNA or streptavidin pairs). 27,28 Although the local distance between plasmonic nanostructures and uorophores can be controlled by using these space layers, the attachment of uorophores on the surface of plasmonic structures is either difficult, time consuming or unstable as uorophores are basically incorporated with plasmonic nanostructures via non-covalent interaction or physical adsorption methods, [29][30][31] which would inevitably limit the practical application of PEF in harsh conditions (e.g. high temperature, strong acid medium, etc.)…”
mentioning
confidence: 99%